Lymph node lymphatic endothelial cells as multifaceted gatekeepers in the immune system - Takeda Akira; Salmi Marko; Jalkanen Sirpa (Elsevier, 2023)
Single-cell technologies have recently allowed the identification of multiple lymphatic endothelial cell (LEC) subsets in subcapsular, paracortical, medullary, and other lymph node (LN) sinus systems in mice and humans. New analyses show that LECs serve key immunological functions in the LN stroma during immune responses. We discuss the roles of different LEC types in guiding leukocyte and cancer cell trafficking to and from the LN parenchyma, in capturing microbes, and in transporting, presenting, and storing lymph-borne antigens in distinct types of lymphatic sinuses. We underscore specific adaptations of human LECs and raise unanswered questions concerning LEC functions in human disease. Despite our limited understanding of human lymphatics - hampering clinical translation in inflammation and metastasis - we support the potential of LN LECs as putative targets for boosting/inhibiting immunoreactivity.